2016
DOI: 10.1002/2015gc006114
|View full text |Cite
|
Sign up to set email alerts
|

Small‐scale spatial variation in near‐surface turbidites around the JFAST site near the Japan Trench

Abstract: This paper aims to improve our understanding of the depositional processes associated with turbidites related to recent earthquake events. A series of short sediment cores (ca. 20–30 cm long) were recovered from the landward slope of the Japan Trench around JFAST (Japan Trench Fast Drilling Project) site C0019 by a remotely operated vehicle, KAIKO 7000 II, and the sample sites were accurately located using an LBL (long base line) acoustic navigation system. The properties of the cores were analyzed using visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Also shown are previous IODP/ODP/DSDP drilling sites in the region and sites where surface cores and/or conventional (as long as 10 m) gravity and piston cores were retrieved after the 2011 earthquake. Solid red symbols = core locations with water depth >100 m where recent publications (Arai et al, 2013;Ikehara et al, 2014Ikehara et al, , 2016Ikehara et al, , 2018Kioka et al, 2019, submitted;McHugh et al, 2016;Noguchi et al, 2012;Nomaki et al, 2016;Oguri et al, 2013;Strasser et al, 2013;Usami et al, 2017Usami et al, , 2018Yoshikawa et al, 2016) or preliminary results from the most recent Sonne Cruise SO-251 (Strasser et al, 2017) document various distinct earthquake-related event deposits or stratigraphic gaps (Molenaar et al, 2019) Figure F2. Stratigraphic correlation between cores from isolated trench-fill basins in the central part of the Japan Trench (between 37°40′N and 38°10′N; alongtrench axis distance = ~50 km).…”
Section: Research Planning: Sampling and Data Sharing Strategymentioning
confidence: 97%
See 1 more Smart Citation
“…Also shown are previous IODP/ODP/DSDP drilling sites in the region and sites where surface cores and/or conventional (as long as 10 m) gravity and piston cores were retrieved after the 2011 earthquake. Solid red symbols = core locations with water depth >100 m where recent publications (Arai et al, 2013;Ikehara et al, 2014Ikehara et al, , 2016Ikehara et al, , 2018Kioka et al, 2019, submitted;McHugh et al, 2016;Noguchi et al, 2012;Nomaki et al, 2016;Oguri et al, 2013;Strasser et al, 2013;Usami et al, 2017Usami et al, , 2018Yoshikawa et al, 2016) or preliminary results from the most recent Sonne Cruise SO-251 (Strasser et al, 2017) document various distinct earthquake-related event deposits or stratigraphic gaps (Molenaar et al, 2019) Figure F2. Stratigraphic correlation between cores from isolated trench-fill basins in the central part of the Japan Trench (between 37°40′N and 38°10′N; alongtrench axis distance = ~50 km).…”
Section: Research Planning: Sampling and Data Sharing Strategymentioning
confidence: 97%
“…Correlation of the event deposit to the 2011 earthquake has been proved positive by short-lived radionuclide (Oguri et al, 2013;McHugh et al, 2016;Ikehara et al, 2016;Kioka et al, 2019) and transient disequilibrium pore water profiles (Strasser et al, 2013). Although there is local variability in deposition and preservation of the event layers (Yoshikawa et al, 2016;Ikehara et al, 2018), the general pattern obtained from >70 cores revealed a good along-strike correlation of documented event deposit occurrence within the reconstructed rupture area (McHugh et al, 2016, Ikehara et al, 2018Kioka et al, 2019). Extensive research is still ongoing to further calibrate the sedimentary record of the 2011 Tohoku-Oki earthquake and assess what earthquake parameters can reliably be deduced from the geological record, making the Japan Trench among the best study areas for calibration of submarine paleoseismology.…”
Section: Japan Trenchmentioning
confidence: 99%
“…Also shown are previous IODP/Integrated Ocean Drilling Progam/ODP/DSDP drilling sites in the region and sites where surface cores and/or conventional (as long as 10 m) gravity and piston cores were retrieved between the 2011 earthquake and 2019. Solid red symbols = core locations with water depth >100 m where recent publications (Arai et al, 2013;Ikehara et al, 2014Ikehara et al, , 2016Ikehara et al, , 2018Kioka et al, 2019aKioka et al, , 2019bMcHugh et al, 2016;Noguchi et al, 2012;Nomaki et al, 2016;Oguri et al 2013;Strasser et al, 2013;Usami et al, 2017Usami et al, , 2018Yoshikawa et al, 2016) or preliminary results from the most recent Sonne Cruise SO-251 (Strasser et al, 2017) document various distinct earthquake-related event deposits or stratigraphic gaps (Molenaar et al, 2019) linked to the 2011 earthquake and tsunami; open red symbols = locations where core data reveal no indication for recent sediment deposition (or erosion) related to the 2011 earthquake and tsunami as documented by Fink et al (2014), Ikehara et al (2016), Yoshikawa et al (2016), and Kioka et al (2019b); black symbols = location of cores for which no detailed information is available; cross symbols = sediment-trapped ocean-bottom seismometers (OBSs) or buried/displaced ocean-bottom pressure recorders (OBPs) associated with the 2011 earthquake (Arai et al, 2013;Miura et al, 2014). JMA = Japan Meteorological Agency.…”
Section: Japan Trench Paleoseismologymentioning
confidence: 99%
“…Correlation of the event deposit to the 2011 earthquake has been proved positive by short-lived radionuclide (Oguri et al, 2013;McHugh et al, 2016McHugh et al, , 2020Ikehara et al, 2016Ikehara et al, , 2021Kioka et al, 2019b) and transient disequilibrium pore water profiles (Strasser et al, 2013). Although there is local variability in deposition and preservation of the event layers (Yoshikawa et al, 2016;Ikehara et al, 2018Ikehara et al, , 2021, the general pattern obtained from >70 cores revealed a good along-strike correlation of documented event deposit occurrence within the reconstructed rupture area (McHugh et al, 2016;Ikehara et al, 2018;Kioka et al, 2019b). Extensive research is still ongoing to further calibrate the sedimentary record of the 2011 Tohoku-Oki earthquake and assess what earthquake parameters can reliably be deduced from the geological record, making the Japan Trench among the best study areas for calibration of submarine paleoseismology.…”
Section: Japan Trench Paleoseismologymentioning
confidence: 99%